Rhetorics of song: critique, persuasion & education in Woody Guthrie & Martin Hoffman's "Deportees" - Kannan, Vani, author; Doe, Sue, advisor; Langstraat, Lisa, advisor; Mumme, Stephen, committee member (Colorado State University. Libraries, 2014)
This thesis investigates the lyrical and musical elements of the song "Deportees," and considers the song's reinterpretation in two contemporary songs. Through autoethnographic writing and rhetorical analysis, I analyze the way all three texts respond to silences in popular media, and in doing so, shed light on the nationalistic ideologies embedded in that silence. I argue that the songs' preservation and circulation of marginalized histories and the performance practices through which they circulate suggest their rich rhetorical and pedagogical potential to inform scholarship in rhetoric and composition. I conclude that transnational feminist analysis and production of song texts and autoethnographic writing can support rhetoric and composition's commitment to social justice by offering guidelines for composing critical texts that respond to silences in the historical record, and allow students and scholars to "write themselves into" transnational events.
Keywords: immigration; citizenship; composition; music; rhetoric; transnational feminism